Congenital Malaria in a 20-Day-Old Neonate: A Case Report and Literature Review - Regasa MT; Shibiru T; Tilahun T; Bayisa G; Negari GK (Dove Medical Press, 2024)
Misganu Teshoma Regasa,1 Tesfaye Shibiru,2 Temesgen Tilahun,3 Gedefa Bayisa,4 Gemechis Kebede Negari2 1Department of Midwifery, Institute of Health Sciences, Wallaga University, Nekemte, Ethiopia; 2Department of Pediatrics and Child Health, School of Medicine, Wallaga University, Nekemte, Ethiopia; 3Department of Obstetrics & Gynecology, Institute of Health Sciences, Wallaga University, Nekemte, Ethiopia; 4Emergency Quality Officer, Wallaga. University Referral Hospital, Wallaga University, Nekemte, EthiopiaCorrespondence: Misganu Teshoma Regasa, Department of Midwifery, Institute of Health Sciences, Wallaga University, P.O Box: 395, Nekemte, Ethiopia, Tel +251917674952, Email misganudule.t@gmail.comBackground: Congenital malaria is a relatively rare condition where the Plasmodium parasite is transmitted from the mother to the fetus during pregnancy. It is associated with a high fatality rate if it is not promptly diagnosed and treated.Case Summary: We report an unusual case of a 20-day-old male baby with Plasmodium vivax malaria from Western Ethiopia, suspected primarily on the basis of positive maternal history that mother had attacks of malaria in the 3rd, 5th, and 8th months of gestation and was cured with artemether-lumefantrine therapy. Infant presented with vomiting and a high-grade fever. The blood film of the baby showed trophozoites stage of Plasmodium vivax with a parasite density of +3. The neonate had severe thrombocytopenia (49,000/micro liter) and Splenomegaly (spleen was palpable 2cm along its line of growth). The patient was admitted to the hospital and treated with artesunate for five days and discharged on the sixth day of admission in stable condition.Conclusion: Sick neonates born to mothers in malaria-endemic areas or with a history of malaria attack(s) in the index pregnancy should be promptly investigated for malaria.Keywords: congenital malaria, case, report, western Ethiopia, plasmodium vivax